Rotary-jet spun polycaprolactone/nano-hydroxyapatite scaffolds modified by simulated body fluid influenced the flexural mode of the neoformed bone - Vasconcellos, Luana M. R. [UNESP]; Elias, Conceicao de M. V.; Minhoto, Giovanna B. [UNESP]; Abdala, Julia M. A.; Andrade, Telmo M.; Araujo, Juliani C. R. de [UNESP]; Gusmao, Suziete Batista Soares; Viana, Bartolomeu C.; Marciano, Fernanda R.; Lobo, Anderson O. (Springer, 2020)
Polycaprolactone (PCL) is a biocompatible, biodegradable synthetic polymer which in combination with nanohydroxyapatite (nHAp) can give rise to a low cost, nontoxic bioactive product with excellent mechanical properties and slow degradation. Here we produced, characterized and evaluated in vivo the bone formation of PCL/nHAp scaffolds produced by the rotary jet spinning technique. The scaffolds produced were firstly soaked into simulated body fluid for 21 days to also obtain nHAp onto PCL/nHAp scaffolds. Afterwards, the scaffolds were characterized by scanning electron microscopy (SEM), energy dispersive spectroscopy and Raman spectroscopy. For in vivo experiments, 20 male Wistar rats were used and randomly divided in 4 experimental groups (n = 5). A critical defect of 3 mm in diameter was made in the tibia of the animals, which were filled with G1 control (clot); G2-PCL scaffold; G3-PCL/nHAp (5%) scaffold; G4-PCL/nHAp (20%) scaffold. All animals were euthanized 60 days after surgery, and the bone repair in the right tibiae were evaluated by radiographic analysis, histological analysis and histomorphometric analysis. While in the left tibias, the areas of bone repair were submitted to the flexural strength test. Radiographic and histomorphometric analyses no showed statistical difference in new bone formation between the groups, but in the three-point flexural tests, the PCL/nHAp (20%) scaffold positively influenced the flexural mode of the neoformed bone. These findings indicate that PCL/nHAp (20%) scaffold improve biomechanical properties of neoformed bone and could be used for bone medicine regenerative.